The AP-1 transcription factor Fosl-2 drives cardiac fibrosis and arrhythmias under immunofibrotic conditions - Mara Stellato; Matthias Dewenter; Michal Rudnik; Amela Hukara; Çagla Özsoy; Florian Renoux; Elena Pachera; Felix Gantenbein; Petra Seebeck; Siim Uhtjaerv; Elena Osto; Daniel Razansky; et al. (Communications Biology, 2023)
The role of the transcription factor Fosl-2 in promoting myocardial fibrosis, arrhythmias and aberrant response to stress under immunofibrotic conditions is described using an in vivo mouse model and human cardiac fibroblasts.